Thermodynamic Casimir effect for films in the three-dimensional Ising universality class: symmetry-breaking boundary conditions - Hasenbusch, Martin (Physical review. B, Condensed matter and materials physics, 2010)
We study the thermodynamic Casimir force for films in the three-dimensional Ising universality class with symmetry-breaking boundary conditions. To this end we simulate the improved Blume-Capel model on the simple cubic lattice. We study the two cases ++, where all spins at the boundary are fixed to +1 and +−, where the spins at one boundary are fixed to +1 while those at the other boundary are fixed to −1. An important issue in analyzing Monte Carlo and experimental data are corrections to scaling. Since we simulate an improved model, leading corrections to scaling, which are proportional to L−ω0, where L0 is the thickness of the film and ω≈0.8, can be ignored. This allows us to focus on corrections to scaling that are caused by the boundary conditions. The analysis of our data shows that these corrections can be accounted for by an effective thickness L0,eff=L0+Ls. Studying the correlation length of the films, the energy per area, the magnetization profile, and the thermodynamic Casimir force at the bulk critical point we find Ls=1.9(1) for our model and the boundary conditions discussed here. Using this result for Ls we find a nice collapse of the finite-size scaling curves obtained for the thicknesses L0=8.5, 16.5, and 32.5 for the full range of temperatures that we consider. We compare our results for the finite-size scaling functions θ++ and θ+− of the thermodynamic Casimir force with those obtained in a previous Monte Carlo study, by the de Gennes-Fisher local-functional method, field theoretic methods, and an experiment with a classical binary liquid mixture
Gesehen am 09.09.2022